The impact of certain flavourings and preservatives on the survivability of eggs of Ascaris suum and Trichuris suis - Boyko, O. O.; Brygadyrenko, V. V. (Regulatory Mechanisms in Biosystems, 2020)
The article describes a laboratory study of nematocidal properties of flavourings with antibacterial effect against Ascaris suum (Goeze, 1782) and Trichuris suis Schrank, 1788. In the experiments, eight concentrations of food additives with antibacterial properties were used: cinnamaldehyde, benzoic acid, formic acid, linalool, citral, β-ionone. Minimum LC50 value for eggs of A. suum was observed while using cinnamaldehyde and benzoic acid – 1.62 ± 0.37% and 1.69 ± 0.14%, and for eggs of T. suis – 0.57 ± 0.03% and 1.80 ± 0.11% respectively. The lowest influence on the development of eggs of nematodes of pigs’ A. suum and T. suis was exerted by formic acid, linalool, citral and β-ionone. In eggs of A. suum and T. suis, larvae formed in 21 and 50 days even during exposure to 3% emulsions of these substances. The strongest negative impact on the eggs of parasitic nematodes was displayed by cinnamaldehyde flavouring. Further study on nematocidal properties of flavourings, as well as their mixtures, would contribute to the development of preparations which would have a strong effect on eggs and larvae of nematodes of animals and humans.